Behavioural entrepreneurial mindset: How entrepreneurial education activity impacts entrepreneurial intention and behaviour. Issue 2 (July 2022) - Cui, Jun; Bell, Robin
Abstract: This research investigates how entrepreneurial education activity (EEA) influences entrepreneurial behaviour (EB) by unpacking how EEA influences both entrepreneurial intention (EI) and EB and how behavioural entrepreneurial mindset (BEM) mediates the relationship between EEA and EI. This furthers research into the behavioural subdimension of entrepreneurial mindset and how this impacts the relationship between EEA and EI. Confirmatory factor analysis was used for checking the measurement model fit and psychometric properties of the measurement scales used, and structural equation modelling was used for testing the proposed model using questionnaire data collected from 1428 students participating in EEA in higher education institutions in China. The research found that effective EEA has a positive effect on EB which was partly mediated by EI, and that EEA positively affects BEM, which in turn mediates the relationship between EEA and EI. This research contributes by expanding the understanding of how EEA can influence students' EB by highlighting BEM as an impact indicator of entrepreneurship education (EE). Secondly, it contributes to the understanding of the formation of students' EB by identifying how BEM mediates the transition from EEA to EB through the development of EI. This highlights BEM as an effective endogenous driver of students' EI, addressing a lacuna in research by investigating EM from the behavioural perspective in EE research. Highlights: Behavioral entrepreneurial mindset with six key elements as a novel indicator of the impact of entrepreneurship education. The influence of entrepreneurial education activity on entrepreneurial behavior. The mediation role of behavioral entrepreneurial mindset in the relationship between entrepreneurial education activity and entrepreneurial intention. The mediation role of entrepreneurial intention in the relationship between entrepreneurial education activity and entrepreneurial behavior. Behavioral entrepreneurial mindset as an effective endogenous driver of students' entrepreneurial intention and its subsequent behavior.